Contribution of Genetic Factors to Sjögren's Syndrome and Sjögren's Syndrome Related Lymphomagenesis. (15th October 2015) - Nezos, Adrianos; Mavragani, Clio P.
Abstract : We aimed to summarize the current evidence related to the contributory role of genetic factors in the pathogenesis of Sjögren's syndrome (SS) and SS-related lymphoma. Genes within the major histocompatibility complex (MHC) locus previously considered conferring increased susceptibility to SS development have been also revealed as important contributors in recent genome wide association studies. Moreover, genetic variations outside the MHC locus involving genes in type I interferon pathway, NF- κ B signaling, B- and T-cell function and methylation processes have been shown to be associated with both SS and SS-related lymphoma development. Appreciating the functional implications of SS-related genetic variants could provide further insights into our understanding of SS heterogeneity, allowing the design of tailored therapeutic interventions.